Global, regional, and national burden of ischemic heart disease associated with diet high in sodium from 1990 to 2021, and its projections to 2035: a systematic analysis of the global burden of disease study 2021 - Mao, Yuqin; Wang, Jiong; Xuan, Shaoyan; Wang, Minxiu; Yang, Shu; Wu, Qiuji; Tang, Zhihua (Frontiers in Nutrition, 2025)
Numerous studies have demonstrated an association between high-sodium diet and the incidence of ischemic heart disease (IHD). This study aims to assess the global impact of IHD associated with diet high in sodium from 1990 to 2021. We retrieved relevant data from the Global Burden of Disease Study 2021 (GBD 2021). The data encompassed the number of IHD-related deaths due to high-sodium intake, age-standardized mortality rates (ASMR), disability-adjusted life years (DALYs), and age-standardized DALYs rates (ASDR), all of which were estimated using GBD’s statistical model. Subsequently, we calculated the burden of IHD associated with high-sodium intake for each country and territory, stratified by age, sex, and socio-demographic index (SDI). The Bayesian age-period-cohort (BAPC) model was used to predict future trends of the IHD burden up to 2035. We discovered that excessive dietary sodium intake is associated with an elevated global burden of IHD. Although ASMR and ASDR have declined over time, this situation continues to impede global socioeconomic progress, and this trend might be associated with population growth and aging. These paradoxical trends underscore the urgent necessity for public health policymakers to prioritize the development of sodium reduction strategies customized to regional epidemiological patterns and gender-specific risk profiles.